Awareness of Environmental Pollution among Secondary Level Learners in Nadia District, West Bengal - Bachhar, Subrata; Sarkar., Bijan (IJRDO - Journal of Social Science and Humanities Research, 2016)
According to the The Hon’ble Supreme Court’s direction towards Environmental Education that an awareness of the environment and its protection should be taught as a compulsory subject in school syllabus. As a result an impact has already been noticed on learner towards Environmental Issues. In this connection researchers have taken the present paper aimed at measuring the awareness of secondary level learner towards environmental pollution in Nadia district, West Bengal, India. A survey of 300sample from rural and urban (rural-150 & urban- 150) was selected for the study. One principle variable- ‘awareness towards environmental pollution’ was considered. Five null hypotheses were framed for the study. One questionnaire which consists of 30 multiple choice type questions of five different dimension of pollution indicator was framed for measuring awareness of environmental pollution among secondary students. Test-retest method was used for estimated the reliability ofthe tool.Mean and SD as Descriptive Statistics, and‘t’ test as Inferential Statistics were employed to find out the significance difference among the gender towards environmental pollution. Finally they found significant difference from two null hypotheses. And the awareness level scores were significantly higher in case of urban male and female students.